Post-caesarean section infection burden, antimicrobial resistance pattern, and associated factors at all Africa Leprosy Rehabilitation and Training Center Comprehensive Specialized Hospital, Addis Ababa, Ethiopia - Namuna Ali; Sebsib Neway; Kassu Desta (PLoS ONE, 2025)
Background Surgical site infections are a major concern in maternal healthcare, especially after cesarean sections (CSs), which are among the most common surgical procedures globally. The World Health Organization reports a pooled prevalence of SSIs in low- and middle-income countries at 5.6 per 100 surgical patients. The global incidence of SSIs after CS is approximately 5.63%, with significant variations: 0.15% in China, 8.02% in India, and 12.6% in Nepal. In sub-Saharan Africa, the incidence is 7.3%, while Ethiopia reports rates as high as 10.4%. Risk factors include older age, prolonged hospitalization, and emergency surgeries, with common pathogens being S. aureus and E. coli. Surgical site infections complicate recovery and contribute to maternal morbidity and mortality, particularly in resource-limited settings like Ethiopia, leading to increased hospitalization and healthcare costs. Objective This study aimed to assess the burden of post-cesarean section bacterial infections, antimicrobial resistance pattern, and associated factors among mothers attending postnatal care services. Methods A cross-sectional study was conducted among 226 participants at All ALERT Comprehensive Specialized Hospital from December 1, 2020, to May 30, 2021. Wound swabs were collected, processed for the isolation of bacterial pathogens, and bacterial susceptibility tests were conducted on the isolates following standard procedures. A structured questionnaire was used to identify potential risk factors. Data were entered and analyzed using SPSS software version 20. Statistical significance of associated factors was determined using odds ratios (95% CI). Bivariate and multivariable logistic regression was performed. Results Among the 226 post-cesarean section patients included in the study, 134/226 (59.29%) showed bacterial growth. The predominant bacterial isolates were coagulase -negative Staphylococcus (CONS) 62/134 (46.27%), S. aureus 46/134 (34.33%), and, from Gram-negative bacteria, E. coli 8/134 (5.97%) and Klebsiella species 8/134 (5.97%). The most resistant antibiotics were penicillin, tetracycline, ampicillin, and cefazolin, while the most effective antibiotics included ciprofloxacin, gentamicin, linezolid, and meropenem. Multidrug-resistant bacteria were also identified. Obstructed labor (cephalopelvic disproportion) and maternal education level beyond college were significantly associated with post-cesarean surgical site infections. Conclusion The prevalence of wound infections following CSs at ALERT Comprehensive Specialized Hospital was found to be high. Infections caused by antibiotic-resistant bacteria contribute to increased maternal morbidity, mortality, and healthcare costs. These findings emphasize the urgent need for strict adherence to infection prevention strategies during the preoperative, intraoperative, and postoperative phases. Additionally, ensuring appropriate and effective treatment is crucial to reducing the risk of surgical site infections.